2002
DOI: 10.1161/01.res.0000040397.23817.e5
|View full text |Cite
|
Sign up to set email alerts
|

Smad2 Mediates Transforming Growth Factor-β Induction of Endothelial Nitric Oxide Synthase Expression

Abstract: Abstract-Transforming growth factor-␤ (TGF-␤) increases expression of endothelial nitric oxide synthase (eNOS), although the precise mechanism by which it does so is unclear. We report that Smad2, a transcription factor activated by TGF-␤, mediates TGF-␤ induction of eNOS in endothelial cells. TGF-␤ induces Smad2 translocation from cytoplasm to nucleus, where it directly interacts with a specific region of the eNOS promoter. Overexpression of Smad2 increases basal levels of eNOS, and further increases TGF-␤ st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 65 publications
7
62
0
Order By: Relevance
“…Moreover, S-Eng TGF-␤1 administration (14). This observation is in agreement with the finding that TGF-␤1 regulates eNOS expression (148) and induces vasodilatation in wild-type mice, this vasodilatation being severely impaired in Eng ϩ/Ϫ mice (147). Thus an in vivo overexpression of S-endoglin appears to result in the same phenotype as L-endoglin deficiency, suggesting opposing functional effects of both isoforms on the NO and COX-2 systems.…”
Section: Role Of Other Endoglin Forms In Vascular Physiopathologysupporting
confidence: 86%
“…Moreover, S-Eng TGF-␤1 administration (14). This observation is in agreement with the finding that TGF-␤1 regulates eNOS expression (148) and induces vasodilatation in wild-type mice, this vasodilatation being severely impaired in Eng ϩ/Ϫ mice (147). Thus an in vivo overexpression of S-endoglin appears to result in the same phenotype as L-endoglin deficiency, suggesting opposing functional effects of both isoforms on the NO and COX-2 systems.…”
Section: Role Of Other Endoglin Forms In Vascular Physiopathologysupporting
confidence: 86%
“…This soluble form of endoglin, in turn, decreases the arterial vasodilatation induced by TGF-␤1 and -␤3, which is mediated by NO. Indeed, TGF-␤ receptor activation increases NO formation through increased eNOS expression and activation, 53,54 and sEng attenuates eNOS activation by TGF-␤ by interfering with the Thr495 dephosphorylation of eNOS, thus contributing to decreased NO synthesis. 34 The negative correlations that we found between plasma or whole blood nitrite concentrations and sEng support the suggestion that sEng plays a role in the pathogenesis of preeclampsia by decreasing NO formation.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore focused on the endoglin relationship with SMAD proteins in our experiment. It was demonstrated that SMAD2 inhibits proinflammatory adhesion molecules, such as E-selectin, and at the same time induces eNOS expression 24,28,29) . To the best of our knowledge, there are no in Fig.…”
Section: Discussionmentioning
confidence: 99%